Expression profiling of precuneus layer III cathepsin D-immunopositive pyramidal neurons in mild cognitive impairment and Alzheimer’s disease: Evidence for neuronal signaling vulnerability - He, Bin (J Comp Neurol, 2020)
The precuneus (PreC; Brodmann area 7), a key hub within the default mode network (DMN) displays amyloid and tau-containing neurofibrillary tangle (NFT) pathology during the onset of Alzheimer’s disease (AD). PreC layer III projection neurons contain lysosomal hydrolase cathepsin D (CatD), 14)a marker of neurons vulnerable to NFT pathology. Here we applied single population laser capture microdissection coupled with custom-designed microarray profiling to determine the genetic signature of PreC CatD-positive-layer III neurons accrued from postmortem tissue obtained from the Rush Religious Orders Study (RROS) cases with a premortem clinical diagnosis of no cognitive impairment (NCI), mild cognitive impairment (MCI) and AD. Expression profiling revealed significant differential expression of key transcripts in MCI and AD compared to NCI that underlie signaling defects, including dysregulation of genes within the endosomal-lysosomal and autophagy pathways, cytoskeletal elements, AD-related genes, ionotropic and metabotropic glutamate receptors, cholinergic enzyme and receptors, markers of monoamine neurotransmission as well as steroid-related transcripts. Pervasive defects in both MCI and AD were found in select transcripts within these key gene ontology categories, underscoring the vulnerability of these corticocortical neurons during the onset and progression of dementia. Select PreC dysregulated genes detected via custom-designed microarray analysis were validated using qPCR. In summary, expression profiling of CatD positive PreC layer III neurons revealed significant dysregulation of a mosaic of genes in MCI and AD that were not previously appreciated in terms of their indication of systems-wide signaling defects in a key hub of the DMN.